A Story of Becoming: Entanglement, Settler Ghosts, and Postcolonial Counterstories. (February 2018) - Fitzpatrick, Esther
"Ūkaipo, " she tells me. "Your place of contentment." And there it is—a gift. The gift of a word to story my "belonging" to my place. The gift from my friend, a Māori scholar. The gift of an indigenous Māori word to a Pākehā, the descendent of a colonial New Zealander. I receive this gift as a taonga, a treasure. As a critical autoethnography, this article demonstrates the process of layering the personal story alongside the wider historical and social story, and alongside stories of other peoples, through a Critical Family History. As a strategy of decolonization, the stories are interrogated using critical theory. Cognizant of Smith's seminal work on decolonizing methodologies, this work illuminates the power dynamics embedded in my family stories and indigenous stories and histories are central to the work. I create a factionalized script drawing on data generated through my critical family history research to provide a coherent story and generate the conditions for deep emotional understandings.